2007
DOI: 10.1007/s00192-007-0375-z
|View full text |Cite
|
Sign up to set email alerts
|

Do overactive bladder symptoms improve after repair of anterior vaginal wall prolapse?

Abstract: This study aims to evaluate the changes of overactive bladder symptoms to anterior vaginal wall prolapse repair. Ninety-three consecutive women with symptomatic anterior vaginal wall prolapse >or= stage II and coexistent overactive bladder symptoms were prospectively studied using a urinalysis, urodynamics, King's Health Questionnaire (KHQ), Prolapse Quality of Life (P-QOL) questionnaire and pelvic organ prolapse quantification (POP-Q) system before and 1 year after surgery. All women underwent a standard fasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 30 publications
7
58
0
2
Order By: Relevance
“…All of this most likely reflects the fact that the etiology of urinary symptoms in the setting of POP is multifactorial. And, while others have demonstrated high rates of improvement in these symptoms after repair, 8,9 other pathologies, such as idiopathic OAB, should be considered as part of surgical planning.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…All of this most likely reflects the fact that the etiology of urinary symptoms in the setting of POP is multifactorial. And, while others have demonstrated high rates of improvement in these symptoms after repair, 8,9 other pathologies, such as idiopathic OAB, should be considered as part of surgical planning.…”
Section: Discussionmentioning
confidence: 96%
“…Recent surgical series have published post-operative resolution rates of 55-59% for frequency, and 75-82% for UUI. 8,9 While these studies, and ours, used validated questionnaire instruments to measure urinary symptoms, results are difficult to compare given the different measures used. Our improvement rates may be lower due to the fact that we were specific in analyzing data from women with pre-operative moderate/severe bother (score of 2 or 3), and defining improvement as a decrease of !2 points.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The only symptom related to vaginal prolapse that one can be sure of being relieved of after surgery is the sensation of bulging. Other symptoms related to bowel, bladder, or sexual function among women with prolapse can either be improved [11,[16][17][18], remain unaltered, or even become worse after surgery [19,20]. Against this background, every woman who undergoes surgery for prolapse should be adequately informed about the effects and side effects of the surgery regarding sexual function and functioning of the bladder and the bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have found a significant improvement in OAB symptoms up to 53-82% following surgical repair of POP. 17,18 Of course, the mere presence of POP is not an indication for any treatment at all; it is a quality-oflife decision. Nevertheless, we believe that for patients with Grade 3 and 4 POP with refractory OAB, surgical treatment offers the best chance of symptom amelioration.…”
Section: Discussionmentioning
confidence: 99%